Mathematical Learning Approach for Special Education Pupils: The Effectiveness of Mauselis Board in Improving Adding Skills - Mad Amin, Ali Imran; Tahar, Mohd Mokhtar; Zakaria, Aina Hafizah (Department of Special Education, 2020)
Mathematic learning difficulties are common, significant, and worthy of serious attention. Many issues that have had an impact on bilingual education have also had an impact on Special Education. One of the issues is, adding skill. Adding skill is one of the most crucial skills that every pupil needs to acquire with learning disabilities. The use of ‘MauSeLis Board’ (Maujud-Sebut-Tulis) which means ‘Concrete-Pronounce-Write’ in the classroom has been an effective tool for helping Special Education pupils in building up their skills in adding and reading the numbers aloud. This study investigates the improvement of the pupils with learning disabilities’ adding skill in Mathematic subject at school. The study's sole objective was (i) to identify the Mauselis board's effectiveness in Mathematical subjects among Special Education pupils. The MauSeLis board was invented for teaching and learning purposes based on the Bruner Theory and CRA Model (Concrete-Pictorial-Abstract). The data collection was conducted through pre-test and post-test conducted on 20 pupils with learning disabilities as respondents in Negeri Sembilan, Malaysia. The study found significant differences in terms of their adding-questions scores before and after using MauSelis Board in teaching and learning sessions. Quantitative data were analyzed using descriptive statistics such as frequency and percentage to describe the Pre and Post Test results. The research study's finding showed a positive result as the Special Education pupils who involved in the study showed consistent improvement throughout the sessions. This study also found that MauSeLis Board in teaching and learning sessions is a highly effective approach that develops a deep and better understanding of mathematic skill among the Special Education pupils as well as contributing to active, fun, and meaningful learning session. In conclusion, this study summarises that the teaching and learning approach among special needs pupils should emphasize effective hands-on activities rather than rote learning.